Isotopic dependence in nuclear-nuclear interaction potential and fusion cross-section - V. O. Nesterov (Ядерна фізика та енергетика)
Fusion cross sections and interaction potentials for 58Ni, 64Ni and different tin isotopes were obtained within the semi microscopic framework. The coupling to 2+ and 3- states in the interacting nuclei has been taken into account in the fusion cross sections calculation. Good agreement with experimental data and isotopic depend-ences of nucleon densities, interaction potentials and fusion cross-sections were founded.